2020
DOI: 10.1177/2158244020939536
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Role of Social Networking in Driving M-Commerce: Evaluating the Use of Mobile Phones for Online Shopping and Payment in the Context of Trust

Abstract: The article analyzes the role of driving m-commerce with social networking and therefore provides insight into how the application of mobile apps influences customers’ perceptions on purchasing products online and on the mode of payment. The consumers are engaged in social interactions through the internet by the new opportunities provided by social media. These interactions provide and generate certain values for both businesses and consumers. An upsurge in the application of social media on mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 54 publications
2
31
0
1
Order By: Relevance
“…Another study has explained how this pandemic made the social media to boost m-commerce (Hossain et al , 2020). Also, the number of hours the users are using the mobile phone is also increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study has explained how this pandemic made the social media to boost m-commerce (Hossain et al , 2020). Also, the number of hours the users are using the mobile phone is also increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hossain et al (2020a) found that tight labor market conditions are encouraging unemployed women, in specific, to use smartphones to start their own setups, particularly in the subcontinent. Today, social networking (Hossain et al 2020b) and innovative ideas help to build venture creation, which generate additional economic opportunities for people with low income in the society (Hossain et al, 2020c). Moreover, sustainable development in education would also assist to create better economic prospects (Hossain et al, 2019b).…”
Section: Moderating Role Of Perceived Labor Market Conditionsmentioning
confidence: 99%
“…In 1973, Katz, Gurevitch , and Hass proposed five categories of needs that apply to all media formats: 1) Cognitive needs, 2) Affective needs , 3) Personal integrative needs , 4) Social integrative needs ; and 5) Cathartic needs . Social media U&G research has revealed a broad spectrum of previously unidentified gratifications, including socializing ( Apaolaza et al., 2014 ), documentation ( Sheldon and Bryant, 2016 ), virtual community ( Chen and Kim, 2013 ), interpersonal utility ( Luo and Remus, 2014 ), reciprocity ( Pai and Arnott, 2013 ), expressive information sharing, professional advancement, meeting new people ( Smock et al., 2011 ), career opportunities, global exchange ( Roy, 2009 ), spiritual support, psychological support, and networking ( Anderson, 2011 ), as well as online shopping and purchasing behavior ( Hossain et al., 2020 ; Hossain et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%